The yield curve and macroeconomic dynamics - Peter Hördahl; Oreste Tristani; David Vestin (European Central Bank (ECB), 2007)
We show that microfounded DSGE models with nominal rigidities can be successful in replicating features of bond yield data which have previously been considered puzzling in general equilibrium frameworks. Consistent with empirical evidence, we obtain average holding period returns that are positive, increasing in maturity and sizable, as well as long-maturity bond yields that are almost as volatile as short-term interest rates. At the same time, we are able to fit sample moments of consumption and inflation relatively well. To improve our understanding of these results, we derive analytical solutions for yields that are valid up to a second order approximation and generally applicable, We demonstrate that the improved model performance does not arise directly from the presence of nominal rigidities: ceteris paribus, the introduction of sticky-prices in a simple model tend to reduce premia. Sticky prices help indirectly because they imply (short-run) monetary non-neutrality, so that the policy rule followed by the central bank affects consumption dynamics and the pricing of yields. A very high degree of “interest rate smoothing” in the policy rule is essential for our results.
Keywords: E43; E44; 330; DSGE Models; policy rules; risk premia; second order approximations; Term structure of interest rates; Dynamisches Gleichgewicht; Zinsstruktur; Risikoprämie; Inflationserwartung; Konsumentenverhalten; Preisrigidität; Wirkungsanalyse